RFID Based Toll Booth Management System using Internet of Things - Rashid, Faizan; Abbas, Ghulam (International Journal of Integrated Engineering, 2021)
Automation has played a vital role in the advancement of engineering and science. In recent times, traffic congestion on toll booths has been increasing day by day in countries like Pakistan. In such circumstances, there is a need to upgrade the Toll Booth Management System. A proper gate system is required to install on many organizations and institutions, which are being controlled manually by a security person. This process results in long queues of vehicles at gates, thus taking too much time and results in burning extra fuel of the vehicles. The system is still not secure. In this paper, the idea of making surveillance smart toll booth system that depends on Radio Frequency Identification (RFID) Innovation and online database has been presented. The automated gate system should be installed at every toll booth as a solution to this. After scanning the RFID, the system allows the vehicle to pass through the gate if data is present at the database. Otherwise, the automobile has to get approval from higher authorities. The developed system scans the RFID tag using RFID reader and compares it with database for authentication purposes and then automatically lifts the barrier up if that vehicle is permissible.